Theoretical models and evaluation tools of learning outcomes in Higher Education - Coggi, Cristina (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2016)
Relevant requirement for the University is to define and explain the results, the learning outcomes of students. It’s a problem with a relatively recent history, of which we’ll discuss some steps. Then we’ll propose some elements of reflection about the models that are adopted, on related measurement tools, to finally find new challenges for research.